The Relationship of Diversification Strategy and Value of Cash Holding with Abnormal Returns in Tehran Stock Exchange listed companies - Hassan Hemati; Zohreh Yosefirad (مطالعات تجربی حسابداری مالی, 2011)
The aim of this study is to investigate the relationship between diversification strategy and cash holding with abnormal return of TSE listed companies. For this purpose, three hypotheses were developed to investigate the relationship between diversification strategy and cash holding with abnormal return of companies and the sample data were extracted from financial statement of listed Companies during the period 2004 to 2008. Results revealed that there is a negative and significant relationship between abnormal returns and diversification strategy, but relationship between abnormal returns and cash holding was not statistically significant. The results also revealed that diversification strategy has positive and significant impact on the relation between abnormal returns and cash balance.